AraC-XylS database: a family of positive transcriptional regulators in bacteria - Tobes, Raquel (Oxford University Press, 2002)
The AraC-XylS database contains information about a family of positive transcriptional regulators broadly distributed in bacteria. This specific database focuses on protein sequences and on the biological and functional features of each of the proteins that belong to this family. Each entry provides information on the protein itself, the annotated protein sequence and, when the crystal is available, a comprehensive representation of its three-dimensional structure. The organization of the database is based on an exhaustive analysis of the scientific literature. The data are interconnected and linked with other databases. Multiple alignments of the members of the family, an extensive collection of references and a tutorial about the family provide additional information. The AraC-XylS database is accessible on the World Wide Web at http://www.AraC-XylS.org.